Characterizations of acoustical porous media: standardized methods, current trends and challenges - Jaouen, Luc; Bécot, François-Xavier; Chevillotte, Fabien (Frontiers in Acoustics, 2025)
Understanding and predicting the vibro-acoustic behavior of acoustical porous materials (like foams, synthetic or natural fibers, metamaterials...) requires to determine the parameters of their solid and their fluid phases. This work presents an non-exhaustive overview of the methods commonly used to assess the visco-elastic and acoustic parameters of such acoustic porous media. A first part is dedicated to identify the parameters related to the dissipation in the fluid phase while a second part focuses on the identification of the parameters related to the solid phase (also called the skeleton). The perspectives related to the characterization of acoustical porous media are also depicted, particularly in the context of recent and ongoing standardization developments.